From patriarchy to electoral quotas: affirmative actions for gender equality: - Rizzoli, Lucimara; Silva, Angela Maria Caulyt Santos da (Argumentum, 2022)
The debate on gender equality in patriarchal societies can enhance the right to emancipation for women. The text reflects on patriarchal society and how gender inequality presents in political-party representation in the Metropolitan Region of Vitória – ES. It is qualitative, documentary, bibliographic and empirical research based on 15 women: state representatives elected in 2014 and re-elected in 2018; the deputy governor, in 2018; and councillors, in 2016. Interviews, semi-structured script, and content analysis were employed. Based on the perceptions of these parliamentary representatives, we discussed the following categories: Patriarchate and Gender Inequality and Quotas as Affirmative Actions. It concludes that although women have gained social and political rights, effective inspection and equity for electoral quotas are necessary.